Maximizing the utility of peer support in carceral settings: A few stumbling blocks to consider. (July 2022) - Perrin, Christian
Emerging research advocates prison-based peer support programmes not only for the recipients of support but also for those providing it. Such programmes are founded on principles such as reciprocity, shared problem-solving and empathy. Accordingly, there have been recent claims that such structures may engender a magnified impact in carceral settings characterized by deprivation and adversity. Specifically, it has been argued that peer supporters garner opportunities to enact prosocial behaviours and consequently energize desistance narratives while serving time. However, as intrigue and optimism around this untapped resource grow, so too does the need to explore any hindrances that might halt progressive developments. This article presents data from qualitative interviews held with incarcerated peer supporters in the UK. Transcripts of the institutional challenges that participants faced when undertaking their roles were thematically analysed, and suggestions for practitioners are offered. The article calls for professionals and policy makers to further explore the redemptive potential of prison-based peer support.